A series of phenyl sulfonate metal coordination polymers as catalysts for one-pot Biginelli reactions under solvent-free conditions. Issue 40 (24th September 2015) - Wang, Jin-Hua; Tang, Gui-Mei; Wang, Yong-Tao; Cui, Yue-Zhi; Wang, Jun-Jie; Ng, Seik Weng
Abstract : A series of phenyl sulfonate metal coordination polymers have been obtained under hydrothermal conditions, which show high catalytic performances for one-pot Biginelli condensation reactions under solvent-free conditions. Abstract : Three new metal coordination polymers, namely, [Co(DPP )2 (H2 O)2 ]·(BS )2 ·2H2 O (1 ), [Co(DPP )2 (H2 O)2 ]·(ABS )2 ·2H2 O (2 ) and [Co(DPP )2 (MBS )2 ] (3 ) [DPP = 1, 3-di(pyridin-4-yl)propane, BS = phenyl sulfonic acid, ABS = p -aminobenzene sulfonic acid, MBS = p -methylbenzene sulfonic acid] were obtained under hydrothermal conditions. Complexes1–3 were structurally characterized using X-ray single-crystal diffraction, XRD and IR spectroscopy. Both complexes1 and2 display a 1D tape structure. Meanwhile, complex3 exhibits a 2D layer and further stacks via C–H⋯π interactions to generate a three-dimensional supramolecular architecture. These three metal coordination polymers have been applied as catalysts for the green synthesis of a variety of 3, 4-dihydropyrimidin-2(1 H )-ones under solvent-free conditions through the Biginelli reaction. Interestingly, the catalysis products have been obtained in high yields under eco-friendly synthesis conditions.